2016
DOI: 10.1097/prs.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Outcomes following Fronto-Orbital Advancement for Metopic Synostosis

Abstract: Background The authors’ purpose is to present changes in anthropometric fronto-orbital dimensions after surgical correction of metopic synostosis. Methods The authors retrospectively analyzed craniometric dimensions in older patients with metopic synostosis corrected by fronto-orbital advancement performed by the senior author (J.B.M.). Preoperative and postoperative linear measures (frontal breadth, cranial width, and intercanthal distance) were taken by direct anthropometry. Interdacryon distance and width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…These techniques are similar to those described by other high-volume craniofacial centers. [5][6][7][8]12,13…”
Section: Surgical Techniques and Postoperative Carementioning
confidence: 99%
See 2 more Smart Citations
“…These techniques are similar to those described by other high-volume craniofacial centers. [5][6][7][8]12,13…”
Section: Surgical Techniques and Postoperative Carementioning
confidence: 99%
“…These observations have led multiple groups to advocate for overcorrection of the deformity at time of initial operation. 12,13 At our institution, we employ a combination of barrel-stave osteotomies, interpositional bone grafts, and/or temporalis muscle flaps to overcorrect frontal width to that of a 6-year-old child. 13 Our techniques are similar to those described by other high-volume centers.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Open CVR is performed using standard FOA techniques for metopic or unicoronal synostosis, and patients with lambdoid synostosis are treated with posterior CVR. 25,30,34 For open CVR, we use a resorbable plating system (SonicWeld, KLS Martin).…”
Section: Treatment Protocol and Techniquementioning
confidence: 99%
“…Other limitations of our study include the sample size and duration of follow-up, as outcomes can vary and show recurrence in 5 to 10 years postoperatively. Longer term studies have demonstrated a trend of temporal hollowing, some of which may be attributed to soft tissue atrophy as well as bone reshaping over time (Fearon et al, 2009; Steinbacher et al, 2011; Seruya et al, 2014; Wes et al, 2014; Patel et al, 2016). We may also not be fully capturing the deformity as we analyzed the contours in a single axial plane 20 mm above the glabella.…”
Section: Discussionmentioning
confidence: 99%